2021
DOI: 10.3389/fcvm.2021.754321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Literacy on Decision Delay in Patients With Acute Myocardial Infarction

Abstract: Background: Health literacy (HL) is a risk factor for adverse outcomes in patients with cardiovascular disease, and shorter pre-hospital delay time is crucial for successful treatment of acute myocardial infraction (AMI) patients. Most previous studies focused on the influencing factors of pre-hospital delay but ignore the essential contribution of decision delay.Aims: Therefore, the purpose of this study was to explore the effect of HL on decision delay.Methods: Continuously included AMI patients admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This study found a negative correlation between the health literacy level of older patients with AIS and delays in medical decision-making. Health literacy is a complex concept that involves many aspects of individual skills [ 43 ]. Patients with high levels of health literacy demonstrate rich motivation, ability, cognition, and social skills to acquire, understand, and apply information to promote and maintain good health [ 44 , 45 ], actively manage their own health, and making timely medical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This study found a negative correlation between the health literacy level of older patients with AIS and delays in medical decision-making. Health literacy is a complex concept that involves many aspects of individual skills [ 43 ]. Patients with high levels of health literacy demonstrate rich motivation, ability, cognition, and social skills to acquire, understand, and apply information to promote and maintain good health [ 44 , 45 ], actively manage their own health, and making timely medical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with limited awareness of their symptoms may underestimate the severity of their condition, leading to delays in seeking treatment [ 20 ]. A study conducted in Tanzania suggested that many individuals delayed seeking treatment due to a lack of understanding about their diagnosis or treatment, a lack of awareness regarding the severity of their symptoms, or concerns about the side effects of medication [ 21 ].…”
Section: Discussionmentioning
confidence: 99%